Implementing Brainstorming Techniques to Improve Arabic Speaking Skills among Secondary School Students - Ilyas Rifa'i; Abdul Hadi; Ilyas Maulana Faqih (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2025)
This study investigates the effectiveness of the brainstorming technique in enhancing Arabic speaking skills among eleventh-grade students at Al-Rasyidiyah Islamic High School, Bandung. Speaking is a crucial component of language learning, yet students often struggle due to traditional, non-interactive teaching methods. Adopting a quasi-experimental design, the study involved two groups: an experimental group taught using the brainstorming technique and a control group taught through conventional methods. Data were collected using pre-tests, post-tests, and observations, then analyzed using descriptive and inferential statistics. Results revealed that the students’ pre-test average score was 49.06 (low category), while their post-test score increased to 76.88 (sufficient category), indicating significant improvement. The t-test analysis showed a calculated t-value of 14.4, which exceeds the critical t-table value of 1.55 at a 0.05 significance level, confirming the statistical significance of the results. Furthermore, the normalized gain (N-Gain) was 0.57 (57%), categorized as a moderate to high improvement. These findings demonstrate that the brainstorming technique effectively enhances students’ Arabic speaking skills by fostering creativity and active participation. The study recommends integrating brainstorming into Arabic language instruction to promote more dynamic, communicative, and student-centered learning experiences